Еще раз о технологической проходимости лесных машин - Vasilyev A. S., Kuznetsov A. V. (Science, education, society: tendencies and future development, 2017)
one of the important indicators characterizing the efficiency of forest machines functioning is their isolation - their passability for logging operations and for forest transportation. It is proposed to use the coefficient of technological patency.
Keywords: лесные машины; транспорт леса; лесосечные работы; logging; forest machines; технологическая проходимость; technological patency; forest transport